1980
DOI: 10.1017/s0021859600028859
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the critical size theory for particles leaving the rumen

Abstract: Three grasses and two legumes, each at two stages of maturity, were fed to three fistulated sheep and samples of the feed, and faeces and contents of the reticulorumen, abomasum and ileum were collected for the determination of particle size by wet sieving. Modulus of fineness (MF) was calculated for all particulate matter that failed to pass a 0-15 mm screen. Resistance to flow from the rumen of feed particles of different sizes was also calculated.The mean MF of the reticulo-rumen contents was 2-56 compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
2
14

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(193 citation statements)
references
References 9 publications
(10 reference statements)
8
165
2
14
Order By: Relevance
“…Although the physical size degradation of particles beyond the fore-stomach is usually of low 310 magnitude in ruminants and macropods (Poppi et al, 1980; Freudenberger, 1992), we 311 observed finer digesta in rectum than fore-stomach contents in wallabies. 312…”
Section: Differences Along the Intestinal Tract 298mentioning
confidence: 55%
“…Although the physical size degradation of particles beyond the fore-stomach is usually of low 310 magnitude in ruminants and macropods (Poppi et al, 1980; Freudenberger, 1992), we 311 observed finer digesta in rectum than fore-stomach contents in wallabies. 312…”
Section: Differences Along the Intestinal Tract 298mentioning
confidence: 55%
“…Very LP was defined as those equivalent to twice the 95 percentile particle length and width values. Poppi et al (1980) reported that the critical particle size in sheep fed different forage maturities is 1.18 mm; particles larger than this are supposed to be retained in the rumen. However, we found that feeding EH led to a higher proportion of particles longer than 1 mm and a tendency towards a higher 95 percentile particle size value in faeces, compared with MH and LH.…”
Section: Chewing Activitymentioning
confidence: 99%
“…Advancing -E-mail: alja@life.ku.dk stage of maturity of grass at harvest and increased lignification of forage NDF have been shown to increase both the mean rumination time per kg of NDF and the mean faecal particle size (Shaver et al, 1988;Rustas et al, 2010). The critical threshold for feed particles to leave the rumen in sheep is less than 1 mm (Poppi et al, 1980). Consequently, the physical breakdown of large rumen particles during rumination is important for the clearance of digesta from the rumen and continued feed intake (Ulyatt et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Algumas partículas com mais de 5 mm podem escapar do rúmen, no entanto, Poppi et al (1980Poppi et al ( , 1981 observaram que menos que 5 % das partículas de fezes de ovinos e bovinos passam por uma peneira de 1,18 mm. A maioria dos modelos usa estes valores.…”
Section: (Recebido Para Publicação Em 6 De Abril De 2004 E Aprovado Eunclassified
“…Poppi et al (1980), porém, sugeriu que um sistema com dois compartimentos para PG e PP oferece melhor quantificação dos processos envolvidos na redução de partículas. Sauvant et al (1996) afirmam que o uso de mais de dois tamanhos prejudicaria o desempenho do modelo, porque aumenta o problema da falta de informação sobre os fluxos entre compartimentos.…”
Section: Pgrunclassified